2020
DOI: 10.1016/j.ihj.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Control of hypertension among teachers in schools in Kerala (CHATS-K), India

Abstract: Objective We investigated the prevalence, awareness, treatment, control of hypertension and the factors associated with hypertension prevalence and control among school teachers in Kerala, India. Methods We surveyed 2216 school teachers in Thiruvananthapuram district of Kerala as part of the control of hypertension among teachers in schools in Kerala (CHATS-K), India. We used World Health Organization STEPS tools for non-communicable diseases risk factor surveillance. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…There were 12 studies (32%) that reported poorer control rates among males than females 20,32,33,36,41,43,45,[49][50][51]53,54 while only three studies showed females to have a poorer control rate than males. 24,31,44 Four studies (11%) reported poorer control rates among rural patients 43,45,47,54 while two studies showed there was no difference in control rate between rural and urban patients.…”
Section: Reporting Of Control Ratesmentioning
confidence: 99%
“…There were 12 studies (32%) that reported poorer control rates among males than females 20,32,33,36,41,43,45,[49][50][51]53,54 while only three studies showed females to have a poorer control rate than males. 24,31,44 Four studies (11%) reported poorer control rates among rural patients 43,45,47,54 while two studies showed there was no difference in control rate between rural and urban patients.…”
Section: Reporting Of Control Ratesmentioning
confidence: 99%
“…We screened 2216 schoolteachers from 92 schools and identified 402 teachers with hypertension implying a hypertension prevalence of 18.1%, 16 much lower than anticipated. We randomly assigned 92 schools equally into usual care and intervention groups using computer‐generated random sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The average of the second and third readings was taken as the final BP reading. The details of data collection have been published previously, 13 and we have also reported the findings of the baseline survey, 16 which informed the design of this randomized controlled trial for hypertension control.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, respondents' mean prevention practices score and standard deviation was 15.34±4.95. This was categorized into low (0-8), moderate (9)(10)(11)(12)(13)(14)(15)(16), and high (17)(18)(19)(20)(21)(22)(23)(24). Less than half 192 (45.9%) of the respondents had high prevention practices while one hundred and eighty-four (44.0%) of the respondents had moderate hypertension prevention practices, and only a few 42 (10.0%) of the respondents had low hypertension prevention practices (See table 5).…”
Section: Respondents' Hypertension Prevention Practicesmentioning
confidence: 99%